MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN INPUT PESERTA DIDIK DI SMAN 1 SYAMTALIRA BAYU KABUPATEN ACEH UTARA - Supriariadi (Institut Nahdlatul Ulama Tasikmalaya, 2023)
Currently, competition between educational institutions is getting tougher. Schools must be able to become quality schools. The achievement of this quality is inseparable from the management of the principal as a leader which begins with the input of students with the concepts of planning, organizing, implementing/motivating, monitoring/controlling and evaluating. The purpose of this study namely 1) To describe the form of planning, organizing, implementing, and evaluating the school principals in increasing the input of New New Students (PPDB) at public senior high school Syamtalira Bayu. 2) Describe the supporting and inhibiting factors of the principal in increasing the input of New New Students (PPDB) at public senior high school Syamtalira Bayu. This research is a qualitatif research using a case study type. The subjects in this study were the principal and PPDB committee at SMAN 1 Syamtalira Bayu. Data were collected by participant observation technique, interviews, and documentation. Data stages of data reduction, presentation and verification. Based on data analysis, the result obtained were that the management of the headmaster in increasing the input of students at SMAN 1 Syamtalira Bayu, starting from making careful planning, organizing the principal has divided the duties of each committee. All committees have carried out their duties properly and responsibly. Internal supporting factors for student input include complete school facilities and infrastructure, committees who have a communicative and cooperative attitude in studying technology. While the external supporting factors include support from alumni by conducting socialization with the school. Support from the community, the school held outreach with the community during community activities. Support from sources of students at the SMP/MTs level around the Bayu sub-district. For the internal inhibiting factor, namely the lack of motivation in the motivation to socialize the acceptance of new students. The motivation of senior teachers in the committee is also very less. For external inhibiting factors, namely the tendency of the community to send their children to SMK, there is also a lack of communication between personnel or human resources at public senior high school.